Булла патриарха Николая Мистика из Херсона - Алексеенко, Н.А. (My University, 2004)
N. Alekseenko. Bulla of Patriarch Nikolay the Mystic from Kherson The new find tells us about one more High Hierarch of Byzantine Church whose name could not be found before on Kherson sphragistics antiques. The seal is printed on the quite big disk of slightly irregular shape, ca. 39 mm in diameter. The matrix margin is 35 mm in diameter. The plate is 2 mm thick. The state of preservation is satisfactory. Unfortunately, the molivdovul has considerable losses of metal but it can be exactly attributed because of the sphragistic type and extant text of inscription on the reverse of the seal. As of today we have several seals of Patriarch Nikolay the Mystic. At least two of them belong to his second patriarchate period as well as, evidently, the Kherson bulla.